Social networks, technology and youth from an approach of the body and the emotions - Loayza Javier, Jerjes (2018)
We analyze the new juvenile daily life that re means the body through social networks with a virtual support. For this purpose, we describe the interactions among young people between 15 and 20 years of age belonging to the city of Lima. Through dialogues via the Facebook chat and the Watts App supported among young people, new sensibilities are identified around the body and emotions. There is a need to see and feel the other, overcoming distances and distance between sender and receiver. It also recognizes new ways of breaking links in the litany of the anonymity of virtual bodies, thereby saving suffering in the context of love relationships. Thus, the proliferation of «non-places» as spaces that lead to a contradiction between the isolation of the individual body and access to the social body as virtuality of intense social interaction is perceived.